Impact of a Full Range of Amylose Level on Pasting and Gelling Properties of Barley Starches at High‐Temperature Heating. (27th October 2022) - Ren, Yikai; Liang, Wenxin; Zhong, Yuyue; Hebelstrup, Kim Henrik; Blennow, Andreas; Ai, Yongfeng
Abstract: Pasting and gelling behaviors of barley starches isolated from Cinnamon (waxy of 3.3% apparent amylose; WB), Golden Promise (normal of 26.2% amylose; NB), and amylose‐only (high‐amylose of 97.8% amylose; AO) varieties were examined over 95–140 °C cooking. Gelatinization temperatures of AO starch were significantly higher than those of WB and NB, thereby the former displaying negligible pasting viscosity at 95 °C heating. At 140 °C, AO starch was completely gelatinized and able to develop viscosity, particularly at the final pasting stage. Gel hardness of NB gradually decreased with higher cooking temperatures. After 140 °C cooking and storage, only AO starch formed a gel, exhibiting the largest hardness among the studied gels or pastes. Gelation mechanisms of the barley starches at 95—140 °C cooking were elucidated by visualizing their gel/paste microstructures under scanning electron microscopy. The insightful information on the physicochemical properties of the barley starches possessing 3.3–97.8% amylose will be meaningful for their industrial applications. Abstract : Amylose‐only (97.8% amylose) barley starch exhibits notably different gelatinization, pasting, and gelling properties as compared with those of waxy (3.3% amylose) and normal (26.2% amylose) barley starches. Gelation mechanisms of the barley starches at 95–140 °C cooking are elucidated by visualizing their gel/paste microstructures under scanning electron microscopy.